Завантажити номер одним файлом - Полтавський державний аграрний університет (Scientific Progress & Innovations, 2025)
The scientific journal is included in category B of the List of scientific professional publications of Ukraine, in which the results of thesis papers for Doctor of Sciences, Candidate of Sciences, and Ph.D degrees in agricultural, veterinary, and technical sciences (Order of the Ministry of Education and Science of Ukraine No. 409 of March 17, 2020 and №886 July 02, 2020) 101 – Ecology; 162 – Biotechnology and Bioengineering; 201 – Agronomy; 202 – Plant Protection and Quarantine; 204 – Technology of Production and Processing of Livestock Products; 211 – Veterinary Medicine; 212 – Veterinary hygiene, sanitation and examination; 208 – Agricultural Engineering